(untitled) (Journal of Student Affairs in Africa, 2021)
Academic advising is a High-Impact Practice that supports better outcomes for all students, particularly those encountering structural barriers to success. This paper presents a case study of processes followed in a three-year project (2018–20) at the University of Cape Town (UCT) to conceptualise, design, and start implementing an academic advising system. Three goals were formulated: • to develop conceptual capacity and a theory of academic advising; • to develop an academic advising model responsive to institutional context and student need; and • to develop structures, relationships, tools, and resources to implement a coherent system. An informed grounded theory approach was used to analyse baseline data of existing support and advising at the institution. Data was collected through document and desktop research, interviews with stakeholders, and student focus groups. A monitoring and evaluation framework was developed to track and reflect on progress against the goals. Iterative cycles of data collection, analysis, and reflection took place as implementation started. A key finding was that UCT’s advising structures incline towards a decentralised faculty-based model, complemented by centralised support services that encompass advising functions. Low levels of integration were found, as well as inefficient duplication of services. To address these challenges, the conceptual and operational capacity of the academic advising team needed to be advanced. This was done by assembling a multidisciplinary team, undergoing professional training, and by running a journal club. A promising theoretical approach that emerged was a capability approach to academic advising. A shared model of academic advising was found to be best suited to the institutional context and a three-tiered model operationalised by faculty, professional, and peer advisers, as well as by automated advising tools, was designed. Implementation started through pilot projects. During Covid-19, innovative concept and centralised systems development that connected students to institutional resources, enabling them to practise agency and supporting their ability to achieve despite unprecedented structural barriers, demonstrated the viability of the capability approach adopted for steering further development of the system.